1991
DOI: 10.1037/0096-1523.17.3.603
|View full text |Cite
|
Sign up to set email alerts
|

Visual control of locomotion: Strategies for changing direction and for going over obstacles.

Abstract: Dynamics of gait adjustments required to go over obstacles and to alter direction of locomotion when cued visually were assessed through the measurement of ground reaction forces, muscle activity, and kinematics. The time of appearance of obstacles of varying heights, their position within the step cycle, and cue lights for direction change were varied. Direction change must be planned in the previous step to reduce the acceleration of the body center of mass toward the landing foot to 0. The inability of stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
267
1
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(287 citation statements)
references
References 20 publications
9
267
1
7
Order By: Relevance
“…The onsets of these changes precede the change in walking direction. The body center of mass is displaced in the new direction of travel through appropriate foot placement (Courtine and Schieppati 2003;Patla et al 1991Patla et al , 1999Xu et al 2004). This is accompanied by turning the head in the direction of the upcoming turn.…”
Section: Discussionmentioning
confidence: 99%
“…The onsets of these changes precede the change in walking direction. The body center of mass is displaced in the new direction of travel through appropriate foot placement (Courtine and Schieppati 2003;Patla et al 1991Patla et al , 1999Xu et al 2004). This is accompanied by turning the head in the direction of the upcoming turn.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern can adapt easily to different speeds, 15,17 inclines, [30][31] surfaces such as overground versus treadmill [32][33][34][35] and uneven surfaces. 36 The main objective of the present study was to measure how SCI subjects adapt to changes in the walking speed. Studies of hindlimb locomotion in spinalized cats [37][38][39] have shown that adaptation to increasing treadmill speed was possible, but that this adaptation was limited to a maximal speed varying between 0.8 and 1.0 m/s.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of visual guidance has been examined in anterior-posterior and mediolateral directions (Lyon & Day, 1997), as well as stepping upwards over an obstacle (Patla et al, 1991). However much less is known about the control of stepping down.…”
Section: Introductionmentioning
confidence: 99%